THE ROLE OF DIGITAL TECHNOLOGY IN THE DEVELOPMENT OF ENTERPRISES IN THE EUROPEAN UNION - Marina COBAN (Eastern European Journal of Regional Studies)
The adoption of digital technologies by EU businesses enables them to achieve better performance in terms of productivity, management practices, innovation and has a major impact on the economic growth of European countries. The aim of the paper is the analysis of digital transformation of enterprises in the EU states. We used comparative analysis of existing data from the Eurostat database. Several indicators are analyzed in this paper, such as the degree of digital intensity, the use of Cloud computing, Big data, Artificial intelligence, the share of SMEs that sell online and sell online cross-border in various EU countries. The advantages and disadvantages of e-commerce as well as the problems faced by SMEs in selling online cross-border, such as problems related to returning products, solving complaints and disputes, lack of knowledge of foreign languages were highlighted. Our study provides an overview of the current state of adoption of digital technologies by EU businesses and identifies the main trends of digital technologies progress in different EU countries.